The new chimpanzee a twenty-first-century portrait of our closest kin - Stanford, Craig B. (Craig Britton), 1956- (Harvard University Press, 2018)
The history of research into the lives of wild chimpanzees now spans more than a half-century since Jane Goodall began it all. The past 20 years have seen tremendous advances in our understanding of our closest kin. These include revelations about our very similar genomes, but also many new discoveries about social behavior and ecology. New cultural traditions and forms of tool use, new evidence for the causes of violence, new evidence of patterns of hunting and meat-eating, and much more. Chimpanzees are new and different apes than they were at the close of the last century. The New Chimpanzee synthesizes the findings of the past 20 years and offers new insights and interpretations of what researchers have learned. The New Chimpanzee draws from results of the 7 longest term (25-55 years) research projects from which we've learned the most about the species, augmented by other shorter field projects conducted in recent years, including my own.--